Boron in drug design: Recent advances in the development of new therapeutic agents - Santos Fernandes, Guilherme Felipe [UNESP]; Denny, William Alexander; Dos Santos, Jean Leandro [UNESP] (Elsevier B.V., 2019)
Advances in the field of boron chemistry have expanded the application of this element in Medicinal Chemistry. Boron-containing compounds represent a new class for medicinal chemists to use in their drug designs. Bortezomib (Velcade (R)), a dipeptide boronic acid approved by the FDA in 2003 for treatment of multiple myeloma, paved the way for the discovery of new boron-containing compounds. After its approval, two other boron-containing compounds have been approved, tavaborole (Kerydin (R)) for the treatment of onychomicosis and crisaborole (Eucrisa (R)) for the treatment of mild to moderate atopic dermatitis. A number of boron-containing compounds have been described and evaluated for a plethora of therapeutic applications. The present review is intended to highlight the recent advances related to boron-containing compounds and their therapeutic applications. Here, we focused only in those most biologically active compounds with proven in vitro and/or in vivo efficacy in the therapeutic area published in the last years. (C) 2019 Elsevier Masson SAS. All rights reserved.
Keywords: Boron; Drug design; Boron-containing compounds; Biological activity; Boronic acids; Benzoxaboroles